Afton-a geotechnical pot-pourri - D. H. Stewart; G. J. Reid (Canadian Institute of Mining, Metallurgy and Petroleum, 1988)
"A diversity of structures and rock types in the Aft on pit has resulted in the occurrence of several different types of wall failure. Delivery of ore to the mill has not been affected and safety has not been compromised thanks to effective remedial 1V0rk and to a system of structural mapping, back analyses of failures, groundwater monitoring, and simple movement monitoring. Remedial measures have included artificial support, dewatering (including vacuum-assisted drainage), flattening of slopes and temporary buttressing. This paper describes six different wall failures at Afton and highlights the features of each. Examples given include rates of movement, extent and direction of movement, and piezometric responses. The practical, low-cost monitoring system was sufficient in one case to allow the prediction of date of failure. IntroductionThe Afton copper deposit is located 13 km west of Karnloops, British Columbia and has been mined for nine years out o f an expected eleven-year life. Open pit mining has reached 700 feet below sur face and is designed to proceed to 970 feet below surface by the time the pit is completed. The excavation is in a structurally and lithologically complex environment. Inevitably, some wall failures have occurred but these have been limited to small, manageable failures which have not compromised production or safety. To handle the failures it has been necessary to understand their nature. Of prim e concern has been the rate s of movement, but displacement vectors and hydrology have been monitored as well. The monitoring system is based on EDM surveys and on wire extensometers and plates set across cracks. Water levels have been read in standpipe piezometers. At Afton the emphasis has been on simple, practical, and inexpensive monitoring and because rock type s and structures play such a major role in any failure, detailed geologic al mapping is carried out."